The scientific bases of autocontrol with vibration phase for a resonance beating-vibration system with two degrees of freedom driven by debalances - Tuan, Tran Van; Sanh, Do; Thach, Luu Duc (Vietnam Journal of Mechanics, 1996)
In the paper it is introduced a method for studying dynamics of beating-vibrators by means of digital calculation with the help of the machine in accordance with the needs by the helps of an available auto regulation system operating with high reability.